Incidence of Urinary Tract Infection Among Patients: Systematic Review and Meta-Analysis - Dechasa Adare Mengistu MSc; Addisu Alemu MPH; Abdi Amin Abdukadir MD; Ahmed Mohammed Husen MD; Fila Ahmed MPH; Baredin Mohammed MPH (SAGE Publishing, 2023)
Healthcare-associated infection is one of the most common and severe threats to patients' health and remains a significant challenge for healthcare providers. Among healthcare-associated infections, urinary tract infection (UTI) is one of the most common infections. This study aimed to determine the global incidence of UTI among patients. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guideline was used to perform this systematic review and meta-analysis. The articles were searched from April 4 to August 5, 2022, from electronic databases (Scopus, PubMed, Web of Science, Google Scholar, DOAJ, and MedNar) using Boolean logic operators, MeSH terms, and keywords. The quality of the study was assessed using the JBI Critical Assessment tool. One thousand nine ninety three articles were retrieved from the electronic databases, of which 38 articles conducted on 981 221 patients were included in the current study. The study found the global pooled incidence of UTI accounted for 1.6%. Based on the subgroup analysis by survey period and WHO region, the highest incidence of UTI was reported in the African Region [3.6%] and among studies conducted between 1996 and 2001 [3.7%]. This study revealed the overall pooled incidence of UTI was 1.6%. The highest incidence of UTI (3.6%) was reported in the African region. This indicates that there is a need to implement safety measures.